Does Osteoarthritis of the Ipsilateral Hip Develop After Knee Rotationplasty? A Radiologic Study on Patients with Long-term Survival Undergoing Surgery for Bone Tumors. Issue 10 (October 2020) - Manfrini, M.; Campanacci, L.; Spinnato, P.; Benedetti, M. G.
Abstract: Background: During routine check-ups of long-term surviving knee rotationplasty patients referred to our institute, we noted that the operated limb radiograph showed signs of hip osteoarthritis in some patients, and that one patient reported hip pain. We wondered whether radiographic changes and symptoms are common in patients undergoing rotationplasty due to mechanical or overloading problems during gait. Based on these considerations, we wished to determine how frequently arthrosis or arthritis would arise in the ipsilateral hip to a knee rotationplasty at long-term follow-up. To our knowledge, this issue has not been explored. Clinicians and patients should be aware of any problems that may affect the hip over time that could result in treatment. Questions/purposes: At a minimum of 10 years after rotationplasty, in a single-center series, we therefore asked: (1) What proportion of patients reported hip pain at rest and with activity? (2) What proportion have radiographically visible arthritic changes in the ipsilateral or contralateral hip? (3) What proportion of patients have changes in the hip morphology (femoral rotation, cervicodiaphyseal angle, acetabular angle, osteopenia)? Methods: Between 1986 to 2009, 42 patients underwent rotationplasty in our institute. They represent the 16.5% of a series of 254 children (age 3 to 14 years) affected by high-grade bone sarcomas located in the distal half of the femur. Three more patients were adolescents older than 15 years and were treated with rotationplasty because of the tumor volume and extracompartmental involvement. Of these 45 patients, 14 died of disease at a mean of 37 months; 31 patients were survivors at the time the study was done. Three of these long-term survivors were known to be alive but did not come for a clinic visit in the last 5 years. The remaining 28 patients were invited to participate in a research study on the long-term assessment of rotationplasty, and all agreed to participate. Unfortunately, 10 patients living far from our Institute could not come in the 2 days established for the assessment due to family or work constraints. AP plain radiographs of the pelvis were taken in 17 patients with long-term survival after knee rotationplasty. Patients were positioned in a standard weightbearing position, wearing their own prosthesis. Hip osteoarthritis was assessed using the Croft grading system. The presence of hip pain was assessed with the self-reported Numeric Rating Scale (NRS), with scores ranging from 0 to 10, at rest and during daily life activities. Femoral rotation, osteopenia, the cervicodiaphyseal and the acetabular angles were measured on radiographs. The median (range) age at follow-up was 32 years (22 to 45), the median age at the time of the intervention was 9 years (6 to 17), and the median follow-up duration after surgery was 25 years (11 to 30). Results: One of the 17 patients complained of mild pain (NRS score of 2) in the ipsilateral hip during walking. No other patient claimed to have hip pain at rest or during walking or other daily life activities. Eleven of 17 patients had signs of OA according to the Croft grading system: one had Grade 1 OA, seven had Grade 2, and three had Grade 3. Six patients did not show any sign of OA in the ipsilateral hip. Two patients had Grade 1 OA and one had Grade 2 OA of the contralateral hip. Sixteen patients had femoral external rotation. An increased valgus cervicodiaphyseal angle and acetabular angle were present in 10 and 9 patients, respectively. Osteopenia at the ipsilateral hip when compared with the contralateral, was present in all patients but one, with varying degrees of severity. Conclusions: In this small series, signs of osteoarthritis of the hip ipsilateral to the rotationplasty were present in a high proportion of patients at a minimum follow-up interval of 10 years after surgery, although only one participant reported hip pain. The finding of arthrosis in the hip above a rotationplasty is potentially important because it may be related to gait abnormalities that may modify the hip's morphology over time. It is encouraging that symptomatic hip pain was uncommon in our patients, but this could become more of a clinical problem with longer follow-up and result in therapeutic intervention. Patients (or the parents of patients) undergoing this procedure should be informed that they might develop hip arthritis during young adulthood. Level of Evidence: Level IV, therapeutic study.